Pengaruh Current Ratio Dan Debt To Equity Ratio Terhadap Harga Saham Pada Perusahaan Manufaktur Sub Sektor Semen Yang Terdaftar Di Bursa Efek Indonesia - Tiya Atmaja; Elis Badariah; Fitria Haquei (GEMILANG: Jurnal Manajemen dan Strategi Bisnis, 2022)
This study aims to analyze the effect of the Current Ratio and Debt To Equity Ratio on Stock Prices in Cement Sub-Sector Manufacturing Companies listed on the Indonesia Stock Exchange. The data used in this study were obtained on the Indonesia Stock Exchange. The sample in this study is the Cement Sub-Sector Manufacturing Company. This research is a type of quantitative research, and collected using secondary data, the data processed is 80. The data is processed using Statistical Product and Service Solutions (SPSS) 26. The results of this study are in hypothesis 1 there is a significant influence between the Current Ratio on Stock Prices in The Cement Sub-Sector Manufacturing Company obtained results with a significant level (0.00 < 0.05) having a t-count of 5.284 with a t-table 1,991 Means, t-count > t-table. Hypothesis 2 there is no significant effect between the Debt To Equity ratio on the Stock Price in the Cement Sub-Sector Manufacturing Company, the results are obtained with a significant level (0.061 > 0.05) having a t-count of -1.900 with t-table 1,991 Means, t-count < t-table. And hypothesis 3 there is a significant effect between Current ratio and Debt To Equity Ratio on Stock Prices in Manufacturing Companies in the Cement Sub-Sector which has a significant level (0.000 < 0.05) and an F-count value of 30.154 with a sig = 0, 05. Can be described by the value of F-count 30.154 > F- table 3.11.